PREVALENSI DAN FAKTOR-FAKTOR RISIKO YANG BERHUBUNGAN DENGAN TINGKAT GEJALA DEPRESI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS TANJUNGPURA - ., Henry Hadianto (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Depression is a mental disorder with the highest rates of mortality and morbidity in the world. Medical students have tendency to getdepression. Burdensome and stressful medical education contributes tothe development of depression symptoms among students. Objective:This study aimed to determineÂ the prevalence and risk factors associatedwith depression symptoms level among medical students of TanjungpuraUniversity. Method: This study was analytic observational study with crosssectional approach, held at Tanjungpura University, Medical Faculty fromJanuary till June 2014. Data were collected using general questionnaireand Beck Depression Inventory II, also analyzed with Chi-Square andlogistic regression test. Results: Total samples were 208 students. Mostof subjects were female (57,2%), in the first year of study (35,1%), enteredthrough non-scholarship route (59,1%), living at home with parents(56,7%), had enough financial condition (68,8%), and used emotionfocusedcoping (60,1%). The prevalence of depression symptoms was30,8%, consisted of 15,4% mild depression, 13% moderate depression,and 2,4% severe depression. Depression symptoms were found highest infemale students (36,1%) and second year students (39,4%). Femalestudents had risk two times greater than male students while second yearstudent had risk three times greater than others students to getdepression. Conclusion: Female and second year medical students arethe greatest number of subjects who had depression symptoms. Keywords: Depression, medical students,and prevalence 1. Medical School, Faculty of Medicine, University of Tanjungpura,Pontianak, West Kalimantan. Â 2. Department of Pediatric, Faculty of Medicine, University ofTanjungpura, Pontianak, West Kalimantan.